CADANGAN, KEHILANGAN, DAN AKUMULASI KARBON PADA PERKEBUNAN KELAPA SAWIT DI LAHAN GAMBUT TROPIKA - Maswar Maswar; Oteng Haridjaja; Supiandi Sabiham; Meine van Noordwijk (Jurnal Solum, 2011)
Peat land conversion to oil palm plantation affects carbon stocks and can change a net sink of atmospheric carbon (C) into a net source. The influence of location, type of peat, drainage practices and fertilization is insufficiently known. A study was conducted in West Aceh from May 2008 until October 2009  in oil palm plantations of various age.  Carbon stocks and  C loss were calculated from data of bulk density (BD), ash content, carbon content, and peat depth. A new method for C loss estimates using ash as internal tracer was developed and tested. Peat land characteristics after drainage and conversion to oil palm plantation were investigated by field observation and laboratory analysis of peat soil samples in the laboratory. Results showed that: 1) Distance from the drain influences the rates of: a) water table depth, b) subsidence, with rates of 1,1  to 9,2 cm/year and 22.67 – 57.23% influence of C loss, and c) soil carbon loss. 2) Ash content and bulk density of the peat are related, indicating the partial loss of soil C during compaction. 3) An “internal tracer” estimate of peat C loss yields estimates of CO2 flux up to 48 t CO2-eq ha-1 y-1 for young oil palm, highly correlated with measured rates of subsidence of the surface and water table depth. 4) Patterns of weight loss of surface litter, measured in litter bags, respond to inherent quality (C/N). Some data for oil palm on shallow peat suggest that a net sink for C can be maintained under such conditions.Key words: Carbon stock, carbon loss, carbon accumulation,  oil palm, tropical peat